Comparative gross morphometry evaluations of the gastrointestinal tract of edible bird's-nest swiftlet (Aerodramus fuciphagus) and house swift (Apus nipalensis) - Mat Amin, Fhaisol; Abdul Razak, Intan Shameha; Abu Bakar @ Zakaria, Md Zuki; Kasim, Azhar (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
The comparative gross morphometrical evaluations of the gastrointestinal tract of two species of aerial insectivorous bird from Apodidae family; Edible Bird's-Nest Swiftlet (Aerodramus fuciphagus) and House Swift (Apus nipalensis) were conducted. The results revealed that the actual weight and length as well as the relative weight and length of the esophagus were significantly higher (P≤0.05) in Apus nipalensis as compared to the Aerodramus fuciphagus. The actual weight and length of Apus nipalensis were higher but relatively significantly lower (P≤0.05) compare to Aerodramus fuciphagus. Similarly, the actual weight and length of the duodenum of Apus nipalensis was higher than Aerodramus fuciphagus but the relative weight and length found to be higher (P≤0.05). The values of remaining intestinal segments showed a similar pattern with the duodenum.